CONSTITUTIONAL JURISDICTION REVIEW OF THE EXISTENCE OF INDIGENOUS LAW COMMUNITIES IN INDONESIA - Aisyah Risyat; Riska Muliani; Muhammad Erfa Redhani (Center for Constitutional and Legislative Studies University of Bandar Lampung, 2022)
The purpose of this study is to find out the reasons for the formation of the Indigenous Law Community which are stated to still exist in Indonesia and the reasons why customary law is not codified in Indonesian laws and regulations. Customary law is based on Article 18B paragraph (2) of the 1945 Constitution of the Republic of Indonesia. The research method used in this article is normative legal research or commonly referred to as doctrinal law research that focuses on written regulations. The findings in this article reveal that customary law is not one of the laws in the hierarchy of laws and regulations in Indonesia because customary law is not a written law. Customary law will continue to change according to the desired interests and will ensure a sense of justice for the community because of the problems that exist in the community. Therefore, the codification of customary law iscontrary to the existing law in Indonesia which was made to be valid forever. According to Satjipto Raharjo, there are 4 requirements in Article 18 B paragraph (2) of the 1945 Constitution of the Republic of Indonesia as a form of state power that determines the existence of a Customary Law Community, namely. as long as they are alive, in accordance with the development of society, according to the the principle of the unitary state of the republic of Indonesia and regulated by law.